Manajemen Literasi Digital Sekolah Dasar Abad 21 - Sunarti, Tri; Hidayati, Dian; Hasanah, Enung (UMSU, 2024)
The contemporary progress of the world has ushered in the era of the industrial revolution, where human existence revolves around information. Consequently, preparing graduates with high competence, capable of global competition, and adept at mastering technological advancements is imperative for individuals and the future of a nation. In the epoch of globalization, the global initiative for the school literacy movement aims to metamorphose educational institutions into literate learning hubs. Primary educational establishments, particularly elementary schools, play a pivotal role in shaping a generation poised to confront myriad challenges. Hence, fostering a novel digital culture is paramount in the modern educational landscape, facilitating the construction of a stronger national identity and readiness for the 21st-century global education era. This article aims to explore the avenues for cultivating students' personalities as lifelong learners through digital literacy, equipping them to navigate the nuances of 21st-century education and thrive in the globalized learning landscape. Employing a qualitative descriptive approach, this study elucidates phenomena in the contemporary environment, gathering data through observations, interviews, and document analysis.